P53 and RB1 regulate Hedgehog responsiveness via autophagy-mediated ciliogenesis. (1st November 2020) - Cain, Jason E.; Watkins, D. Neil
ABSTRACT: Loss of tumor protein p53 (p53) and RB transcriptional corepressor 1 (RB1) in developmental and small cell lung cancer models promotes primary cilia formation and hyper-responsiveness to Hedgehog ligand. This is mediated by impaired transcription of p53 and RB1 target genes involved in autophagic degradation of primary cilia.